2022
DOI: 10.1038/s41396-022-01282-z
|View full text |Cite
|
Sign up to set email alerts
|

α-cyanobacteria possessing form IA RuBisCO globally dominate aquatic habitats

Abstract: RuBisCO (ribulose 1,5-bisphosphate carboxylase/oxygenase) is one the most abundant enzymes on Earth. Virtually all food webs depend on its activity to supply fixed carbon. In aerobic environments, RuBisCO struggles to distinguish efficiently between CO2 and O2. To compensate, organisms have evolved convergent solutions to concentrate CO2 around the active site. The genetic engineering of such inorganic carbon concentrating mechanisms (CCMs) into plants could help facilitate future global food security for huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 91 publications
4
41
0
Order By: Relevance
“…The most complex cyanobacterial genomes were recovered from soils, with genes involved in chemotaxis, membrane transport, motility and phototaxis ( pix gene cluster) being over‐represented in this group. These conclusions are further supported by a study comparing genomes of marine, brackish and freshwater isolates, that showed that both genome sizes (2.5 Mbp vs. 2.9 Mbp) and GC content (64% vs. 58.5%) were smaller in marine genomes compared to freshwater ones (Cabello‐Yeves, Callieri, et al, 2022; Cabello‐Yeves, Scanlan, et al, 2022). NiFe‐hydrogenases were among the genes that were enriched and could be responsible for adaptation to the pelagial of freshwaters, together with pyruvate ferredoxin oxidoreductase genes and the gas‐vesicle synthesis cluster ( gvpLFK ).…”
Section: Prokaryotic Lineages With Known Habitat Transitionsmentioning
confidence: 74%
“…The most complex cyanobacterial genomes were recovered from soils, with genes involved in chemotaxis, membrane transport, motility and phototaxis ( pix gene cluster) being over‐represented in this group. These conclusions are further supported by a study comparing genomes of marine, brackish and freshwater isolates, that showed that both genome sizes (2.5 Mbp vs. 2.9 Mbp) and GC content (64% vs. 58.5%) were smaller in marine genomes compared to freshwater ones (Cabello‐Yeves, Callieri, et al, 2022; Cabello‐Yeves, Scanlan, et al, 2022). NiFe‐hydrogenases were among the genes that were enriched and could be responsible for adaptation to the pelagial of freshwaters, together with pyruvate ferredoxin oxidoreductase genes and the gas‐vesicle synthesis cluster ( gvpLFK ).…”
Section: Prokaryotic Lineages With Known Habitat Transitionsmentioning
confidence: 74%
“…Given the phylogeny of the isolates obtained (see "Phylogeny of the new freshwater picocyanobacterial isolates" section below), this work only compares cluster 5 picocyanobacteria, specifically from the Synechococcus and Cyanobium genera, comprising isolates from different SCs (5.1, 5.2, 5.3) obtained from marine, brackish, and freshwater envionments. A parallel work compares cluster 5 picocyanobacteria (α-cyanobacteria) with other unicellular Synechococcus-like strains (β-cyanobacteria) [47]. We used only complete or near-complete genomes (draft) derived from cultures to reduce to a minimum the bias introduced from incomplete genomes derived from metagenomes (MAGs) and single cells (SAGs).…”
Section: A New Picocyanobacterial Dataset Of Freshwater Brackish and ...mentioning
confidence: 99%
“…Being photoautotrophic, all genomes possessed a gene content consistent with their photosynthetic lifestyle, i.e., possessing photosystems I and II, NAD(P) H dehydrogenase, the cytochrome b6-f complex, ATP synthase, α-carboxysomes, type IA RuBisCOs (ribulose-1.5 biphosphate carboxylase-oxygenase) [47], and phycobilisomes (PBS) (Additional file 13: Table S6). We did note, however, some specific differences in some photosynthesis and light-harvesting genes.…”
Section: Carbon Fixation and Photosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Bacteriocin synthesis clusters have not only been identified in the genomes of bloom-forming filamentous cyanobacteria, but are also present in the genomes of picocyanobacteria with smaller genomes, highlighting their importance for the organism because they are kept despite substantial genome reduction ( Paz-Yepes et al, 2013 ). Recently, it has been shown that such strains occur very frequently in the waters of different salinities including the Baltic Sea in summer ( Cabello-Yeves et al, 2022 ). Since most bloom formation associated genes, such as nitrogenase-related, gas-vesicle, bacteriocin and iron-acquisition genes, became more highly expressed only after 14 days under P-limiting conditions, we conclude that long-term harsh P-starvation can indeed be regarded as a potential trigger for bloom formation in Nodularia CCY9414 and likely other cyanobacteria.…”
Section: Discussionmentioning
confidence: 99%